Clinical peptide vaccination trials for leukemia patients. (June 2011) - Casalegno-Garduñño, R; Schmitt, A; Schmitt, M
The favorable graft-versus-leukemia (GVL) effect that occurs after stem cell transplantation suggests that T cells can eradicate leukemia blasts. T cells specifically recognize peptides and exert an antileukemia effect. Several leukemia-associated antigens (LAAs) have been found to be overexpressed in malignant cells from patients with acute or chronic leukemia leading to the generation of peptide-based leukemia immunotherapy. Peptide vaccination with LAAs, whose expression is low in normal tissue, such as the receptor for hyaluronic acid-mediated motility (RHAMM), Wilms tumor 1 (WT1), proteinase-3 (PR-3) and the breakpoint cluster region-Abelson (bcr-abl) has been reported to induce leukemia-specific T-cell responses in patients with a variety of hematological malignancies. Moreover, the immune responses achieved after vaccination positively correlated with good clinical outcomes, that is complete remission. Large efforts have been made to optimize the dose and format of vaccines, as well as their adjuvants, in small pilot trials. In this article we summarize clinical Phase I and II peptide vaccination trials with RHAMM, WT1, PR-3 and bcr-abl for leukemia patients.